Metal Ion Release, Clinical and Radiological Outcomes in Large Diameter Metal-on-Metal Total Hip Arthroplasty at Long-Term Follow-Up - Pozzuoli, Assunta (Diagnostics (Basel), 2020)
Total hip arthroplasty (THA) with metal-on-metal (MoM) bearings have shown problems of biocompatibility linked to metal ion release at the local level causing an adverse reaction to metal debris (ARMD) and at a systemic level. The aim of this study was to evaluate clinical and radiological outcomes, and metal ion concentrations in the blood and urine of patients who underwent THA with the LIMA Met-Met hip system. Patients with ceramic-on-ceramic (CoC) bearings were included as a control group. In this study, 68 patients were enrolled: 34 with MoM THAs and 34 with CoC THAs. Patients were evaluated clinically (Harris Hip Score, SF-36) and radiologically at a median of 7.4 years after surgery. Whole blood and urinary cobalt and chromium levels were also assessed. Both types of implants were comparable in terms of clinical and functional results. Ion levels were significantly higher in the MoM group compared with CoC group 7 years after surgery. No correlations were found between metal ion levels and patient demographics, functional and radiological outcomes, and prosthesis features. Patient monitoring is thus advised to establish if prosthesis revision is necessary, especially in the case of MoM THA.